Bibliometric analysis of the tertiary study on agile software development using social network analysis - DOĞAN, BUKET (My University, 2020)
This study aims to examine the systematic literature reviews published on the Agile Software Development subject between 2013 and 2018 and to examine the citation relationships among the studies within the scope of the tertiary study with the help of social network analysis. In this study, the publications within the scope were visualized with VOSviewer and Gephi social network analysis tools, and the relations between publishing institutions, countries were revealed. In citation analysis; according to the total link strength, it is seen that UK, Spain and Slovenia are at the forefront at institution and country level. Brazil has the highest citation value and provides the link between the two large clusters obtained in the analysis. In the bibliographic coupling analysis, the five most active countries at the country level were Brazil, Germany, Finland, Malaysia and Pakistan. When the same analysis is made at the institution level, the top five institutions are in Brazil, Switzerland, Peru and Pakistan. The findings of the study indicate that developing countries have more studies on the subject and that the cited publications are mostly from developed countries; European countries seem to be more collaborative based on citation analysis yet developing countries such as Brazil and Malaysia have also relations with them; the number of publications is not directly proportional to the citations.
Keywords: agile software development; tertiary study; social network analysis; systematic literature reviews; bibliometric analysis